2013
DOI: 10.1007/978-3-319-02753-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Web Use Behaviors for Identifying Mental Health Status

Abstract: Abstract. It is very important to identify mental health problems early and efficiently, but traditional method relies on face-to-face communication which suffers from the limitations in practice. This study aimed to propose an innovative method of detecting mental health problems via web use behaviors. 102 graduates were administrated by SCL-90 questionnaire to get their actual mental health status with 10 dimensions, and their web use behaviors were acquired from Internet access log recorded on the gateway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The model estimates the dimensions’ scores based on online behavior characteristics and linguistic features over the past 7 days. Validation studies showed that the estimated scores and the actual questionnaire scores were moderately correlated, and the Pearson correlation coefficients ranged from 0.49 to 0.65 [ 22 ]. The major advantage of this method is that people’s mental health can be monitored in a timely manner without asking the subjects to repeatedly complete the same set of questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…The model estimates the dimensions’ scores based on online behavior characteristics and linguistic features over the past 7 days. Validation studies showed that the estimated scores and the actual questionnaire scores were moderately correlated, and the Pearson correlation coefficients ranged from 0.49 to 0.65 [ 22 ]. The major advantage of this method is that people’s mental health can be monitored in a timely manner without asking the subjects to repeatedly complete the same set of questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, eHealth engagement as the second gap of the digital divide has also been viewed as a positive factor in improving actual health outcomes according to the theory. For instance, [18] found that Internet use can reduce mental problems among elder adults, and this effect was also observed in younger populations [19]. Additionally, the role of Internet use in improving physical health has been identified as positive in both young and elder populations [20,21].…”
Section: Ehealth Engagement Motivational and Actual Health Outcomesmentioning
confidence: 98%
“…Traditional psychological methods, such as questionnaires, are impractical for the extensive sampling required across China's thirty-plus provinces over a decade. In contrast, social media platforms like Sina Weibo, with its 566 million monthly active users and a dataset extending back to 2010 [38,39], provide a rich source for non-invasive public psychology and behavior analysis through big data analytics of user activities [40][41][42]. By leveraging this extensive dataset, our study employs a validated machine-learning model [4,43,44] to assess SWB based on the text of social media posts.…”
Section: H2: Income Inequality Exerts a Negative Influence On Swb Wit...mentioning
confidence: 99%
“…In this case, Weibo's API facilitated systematic access to and collection of large-scale data from the platform, aiding in the analysis of usergenerated content. For constructing regional Subjective Well-Being (SWB), text data was sourced from an initial pool of over 1.16 million Sina Weibo users [41]. Recognized as China's leading microblogging platform, Sina Weibo promotes the exchange and discussion of personal experiences, lifestyle activities, and celebrity news [45].…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation